Research Writing Competence of Master Teachers and School Heads and its Implications to Research Management - Abara, Marvin Q.; Antonio, Vida V. (Future Science / FSH-PH Publications, 2025)
This study assessed the research writing competence of master teachers and school heads through survey questionnaires and semi-structured interviews. Descriptive data analysis techniques, including frequency counts, percentage distributions, and means were utilized to summarize and interpret the data. The research productivity profile indicated a clear need for additional training to enhance the research skills and knowledge of the educators. A few number of respondents had not undergone research-related training from 2017 to 2021, and a small number had completed research studies, presented research findings at conferences, and published research articles. This highlights the need to improve research generation, dissemination, and publication skills. Regarding research writing competence, self-assessments varied by role and education level. Elementary level master teachers demonstrated moderate competence in writing research, while expressing limited familiarity with knowledge on research methodology. Junior High School (JHS) master teachers and school heads generally perceived themselves as highly competent in various research writing tasks. However, they continued to encounter challenges in certain areas. They displayed high competence in conducting quantitative and qualitative research and in making use of their ICT skills in research. Additionally, they demonstrated a strong understanding of research ethical principles and standards. Overall, the study identified areas for improvement, including connecting research findings with existing literature, establishing research gaps, and enhancing research dissemination and presentation skills. These findings inform the design of targeted training programs and interventions to address these specific areas of improvement among master teachers and school heads, leading to improved research management in schools.